Integrating Social, Cultural, And Moral Values In Indonesian Literature Teaching at Senior High Schools - Aam Nurjaman; Stella Talitha; Khaerudin Kurniawan; Eri Sarimanah; Ainiyah Ekowati (LPPM Universitas PGRI Sumatera Barat, 2025)
This research investigates how social, cultural, and moral values embedded in Indonesian literary texts can be integrated to strengthen literacy in senior high schools. Framed by contemporary conceptions of literacy as critical, reflective, and socio-culturally situated, the study analyzes a curated corpus of Indonesian novels and short stories commonly discussed in secondary-level literary studies (e.g., Bukan Pasar Malam, Perempuan Bersampur Merah, Canai, Sabtu Bersama Bapak). Using a qualitative descriptive approach with a content-analysis design, we conducted intensive readings, coding, and cross-text comparison against value indicators (compassion, responsibility, harmony; respect, hospitality, religiosity; honesty, integrity, perseverance). The analysis yielded 141 value-bearing excerpts: 49 moral, 37 social, and 55 cultural. Results show that (1) moral values are articulated both explicitly (maxims, parental counsel) and implicitly (sacrifice, empathy in action); (2) social values cohere around cooperation, solidarity, and civic contribution; and (3) cultural values foreground family rituals, respect for elders, religious practice, language preservation, and communal cooperation. Pedagogically, these patterns support deep reading and value-rich literacy through reflective writing, dialogic discussion, role-play of ethical dilemmas, and project-based tasks that link texts to learners’ lived contexts. The study contributes a consolidated, text-based rationale for recommending specific Indonesian literary works as classroom resources aligned with the Kurikulum Merdeka and 21st-century literacy goals. Limitations include the bounded corpus and qualitative scope; future work should pilot classroom implementations and mixed-methods evaluations of student outcomes